Right Median Nerve Stimulation for Improving Consciousness: A Case Series - Sharma, Vivek; Kaur, Harraman; Gupta, Divya (Indian Journal of Neurotrauma, 2015)
Brain injury is a leading cause of mortality, morbidity, and socioeconomic losses in India. Despite the improvements in emergency treatment, persistent coma is still a major clinical problem. Regardless of the etiology of the coma or reduced level of awareness, electrical stimulation may serve as a catalyst to enhance central nervous system functions. The right median nerve is a portal to electrically stimulate and help arouse the central nervous system for persons with reduced levels of consciousness. The mechanisms of central action include increased cerebral blood flow and raised levels of norepinephrine and dopamine. We report findings of seven patients who were given right median nerve stimulation to observe its effect on the consciousness.
Keywords: right median nerve stimulation; consciousness; coma